2014
DOI: 10.1016/j.jchf.2014.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Mortality After Cardiac Allograft Vasculopathy

Abstract: Worsening severity of CAV was associated with progressively worse long-term survival among heart transplant recipients. Among patients with CAV, long-term survival in those with CAV amenable to PCI was greater than that in those with severe CAV not treatable with PCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 28 publications
1
32
0
Order By: Relevance
“…An important finding of our study was that not only is early CAV diagnosis at four years associated with decreased long-time survival, but also that even mild coronary lesions, scored as CAV grade 1, represent a negative prognostic factor. Although the majority of studies are directed to more advanced degrees of CAV, which are also amenable to interventions, one other recent report showed that persistent mild coronary lesions have a negative prognostic impact [2, 21]. This finding emphasises the role of preventive measures immediately after transplantation, before even mild coronary disease may develop.…”
Section: Discussionmentioning
confidence: 99%
“…An important finding of our study was that not only is early CAV diagnosis at four years associated with decreased long-time survival, but also that even mild coronary lesions, scored as CAV grade 1, represent a negative prognostic factor. Although the majority of studies are directed to more advanced degrees of CAV, which are also amenable to interventions, one other recent report showed that persistent mild coronary lesions have a negative prognostic impact [2, 21]. This finding emphasises the role of preventive measures immediately after transplantation, before even mild coronary disease may develop.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to those without CAV, patients with mild forms (ISHLT CAV1) have a two-fold risk of death, while patients with severe CAV (ISHLT CAV3) have a 15 times higher mortality. 2 Nevertheless, angiography is limited in its ability to detect CAV because it provides only a “lumengram”, failing to provide information about arterial wall thickening and coronary blood flow. Furthermore, there is significant inter-observer variation in angiographic grading.…”
Section: Invasive Testingmentioning
confidence: 99%
“…92 In a single center study, patients with ISHLT CAV 3 that was amenable to PCI and who underwent PCI had a decreased odds of death at two (OR 0.26, 95% CI 0.08–0.82) and five years (OR 0.28, 95% CI 0.09–0.93) compared to patients with ISHLT CAV 3 not amenable to PCI. 93 Thus it is reasonable to perform PCI for CAV that is amenable to PCI as a palliative treatment.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…5,41,55,64,72 Long-term survival in patients with CAV amenable to PCI is greater than that in those with severe CAV not amenable to PCI. 73 Fewer OHT recipients with CAV are candidates for coronary artery bypass grafting (CABG) than for PCI, but the highly-selective CAV patients undergoing CABG may have favorable outcomes. 5,44,55 CAV is the most common indication for retransplantation, which remains the definitive therapy when CAV is not amenable to revascularizations (Table 3).…”
mentioning
confidence: 99%